End-of-life care in general practice: clinic-based data collection. Issue Volume 12(2022)Issue e1 (17th February 2020) - Ding, Jinfeng; Cook, Angus; Chua, David; Licqurish, Sharon; Woolford, Marta; Deckx, Laura; Mitchell, Geoffrey; Johnson, Claire E
Abstract : Background: There are no processes that routinely assess end-of-life care in Australian general practice. This study aimed to develop a data collection process which could collect observational data on end-of-life care from Australian general practitioners (GPs) via a questionnaire and clinical data from general practice software. Methods: The data collection process was developed based on a modified Delphi study, then pilot tested with GPs through online surveys across three Australian states and data extraction from general practice software, and finally evaluated through participant interviews. Results: The developed data collection process consisted of three questionnaires: Basic Practice Descriptors (32 items), Clinical Data Query (32 items) and GP-completed Questionnaire (21 items). Data extraction from general practice software was performed for 97 decedents of 10 GPs and gathered data on prescriptions, investigations and referral patterns. Reports on care of 272 decedents were provided by 63 GPs. The GP-completed Questionnaire achieved a satisfactory level of validity and reliability. Our interviews with 23 participating GPs demonstrated the feasibility and acceptability of this data collection process in Australian general practice. Conclusions: The data collection process developed and tested in this study is feasible and acceptable for Australian GPs, and comprehensively covers the major components of end-of-life care. Future studies could develop an automated data extraction tool to reduce the time and recall burden for GPs. These findings will help build a nationwide integrated information network for primary end-of-life care in Australia.